Attitudes toward Seeking Professional Psychological Help: Adaptation and Evaluation of ATSPPH-SF using the Rasch Model - F A Nurdiyanto; Ririn Mamiek Wulandari; Griselda Maria Ancela Wodong (Jurnal Psikologi, 2021)
The availability of instruments for seeking professional help is crucial in identifying potential delays and failures to seek mental health help. The current study aims to adapt an Indonesian version of the Attitudes toward Seeking Professional Psychological Help-Short Form (ATSPPH-SF) scale and evaluate its psychometric properties using a Rasch modeling approach. Adaptation of the Indonesian scale was carried out in collaboration with a panel of experts under the guidelines of the International Translating Commission. The psychometric evaluation involved 951 respondents (M = 243, F = 708) who participated through an online survey. The results of the Rasch modeling showed that the items of the Indonesian ATSPPH-SF had a good fit with the model. The response categories worked well and reliability was sufficient (item=1, respondent=.59, Cronbach's alpha=.67). This paper highlighted that the ATSPPH-SF Indonesia version is suggested to be valid and reliable. We concluded that ATSPPH-SF can be used in mental health professional help-seeking research in Indonesia.